2003
DOI: 10.1105/tpc.010926
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and Characterization of the WAX2 Gene of Arabidopsis Involved in Cuticle Membrane and Wax Production

Abstract: Insertional mutagenesis of Arabidopsis ecotype C24 was used to identify a novel mutant, designated wax2 , that had alterations in both cuticle membrane and cuticular waxes. Arabidopsis mutants with altered cuticle membrane have not been reported previously. Compared with the wild type, the cuticle membrane of wax2 stems weighed 20.2% less, and when viewed using electron microscopy, it was 36.4% thicker, less opaque, and structurally disorganized. The total wax amount on wax2 leaves and stems was reduced by Ͼ 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
405
1
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 365 publications
(421 citation statements)
references
References 59 publications
14
405
1
1
Order By: Relevance
“…In agreement with this observation, bacteria transformed with a MS2 cDNA produce fatty alcohols from uncharacterized precursors (Doan et al, 2009). A loss-of-function mutation in the FACELESS POLLEN1/YORE-YORE/WAX2 gene that impacts exine structure and wax synthesis (Ariizumi et al, 2003;Chen et al, 2003;Kurata et al, 2003) was reported recently to be allelic to CER3, a gene previously described to fulfill an unknown function in wax synthesis (Rowland et al, 2007). DIHYDROFLA-VONOL 4-REDUCTASE-LIKE1 (DRL1), another gene required for pollen development and male fertility (Tang et al, 2009), shares sequence similarity with DIHYDROFLAVONOL REDUCTASE (DFR), a gene implicated in the biosynthesis of anthocyanins and proanthocyanidins (Shirley et al, 1992), but the DRL1 enzyme is also of unknown biochemical function.…”
Section: Introductionmentioning
confidence: 56%
“…In agreement with this observation, bacteria transformed with a MS2 cDNA produce fatty alcohols from uncharacterized precursors (Doan et al, 2009). A loss-of-function mutation in the FACELESS POLLEN1/YORE-YORE/WAX2 gene that impacts exine structure and wax synthesis (Ariizumi et al, 2003;Chen et al, 2003;Kurata et al, 2003) was reported recently to be allelic to CER3, a gene previously described to fulfill an unknown function in wax synthesis (Rowland et al, 2007). DIHYDROFLA-VONOL 4-REDUCTASE-LIKE1 (DRL1), another gene required for pollen development and male fertility (Tang et al, 2009), shares sequence similarity with DIHYDROFLAVONOL REDUCTASE (DFR), a gene implicated in the biosynthesis of anthocyanins and proanthocyanidins (Shirley et al, 1992), but the DRL1 enzyme is also of unknown biochemical function.…”
Section: Introductionmentioning
confidence: 56%
“…VLCFA derivatives secreted on the surface of pollen and stigma have been shown to participate in pollen-stigma interaction in various plants (25)(26)(27), including wheat (28) with the lipid-rich pollen coat playing a role in plants with ''dry stigmas'' and lipid-rich secretions on ''wet stigmas'' playing the role in other plants. Our results show a high level of expression of the cytosolic ACC gene on the top surface of the ovary, suggesting an elevated rate of CW secretion by epidermal cells in this part of the organ.…”
Section: Discussionmentioning
confidence: 99%
“…Orchestration of a number of pathways and cell-cell communication are necessary for proper differentiation of protodermal cells (Van Den Berg et al, 1997;Huelskamp and Schnittger, 1998). In Arabidopsis, studies on the FIDDLEHEAD (FDH), HIGH CARBON DIOXIDE (HIC), LACERATA (LCR) and WAX2/YORE-YORE genes have revealed a role for fatty acid metabolism in this process (Yephremov et al, 1999;Pruitt et al, 2000;Wellesen, 2001;Chen et al, 2003;Kurata et al, 2003). The FDH and HIC genes code for putative b-ketoacylCoA synthases of the FATTY ACID ELONGA-TION1 (FAE1) gene family, which consists of 21 genes in Arabidopsis (Lechelt-Kunze et al, 2003).…”
Section: Introductionmentioning
confidence: 99%